Palatal Actinomycosis and Kaposi Sarcoma in an HIV-Infected Subject with Disseminated Mycobacterium avium-intracellulare Infection - Yuria Ablanedo-Terrazas; Christopher E. Ormsby; Gustavo Reyes-Terán (Case Reports in Medicine)
Actinomyces and Mycobacterium avium-intracellulare are facultative intracellular organisms, members of the bacterial order actinomycetales. Although Actinomyces can behave as copathogen when anatomic barriers are compromised, its coinfection with Mycobacterium avium-intracellulare has not previously been reported. We present the first reported case of palatal actinomycosis co-infection with disseminated MAC, in an HIV-infected subject with Kaposi sarcoma and diabetes. We discuss the pathogenesis of the complex condition of this subject.